APPRAISAL OF CONTINUOUS ASSESSMENT MODES IN PUBLIC AND PRIVATE JUNIOR SECONDARY SCHOOLS IN BENIN METROPOLIS - Ogedegbe, Anita Odufa; MATILDA, ORHERUATA U (Sokoto Educational Review, 2023)
The study appraised continuous assessment modes in public and private junior secondary schools in the Benin metropolis. Specifically, the study ascertains if a difference exists in the continuous assessment modes between public and private junior secondary schools in the Benin metropolis. To achieve this, three hypotheses were tested at 0.05 alpha level of significance. The design used for this study was the survey research design using the documentary approach. The population of the study consist of 435 public and private junior secondary schools and 2,357 teachers in public and private junior secondary schools in the Benin metropolis of Edo State. A sample of 420 teachers was selected using a simple random sampling technique through balloting. A Check-list was used as the research instrument. The instrument was validated by experts. In analyzing the data, the chi-square test for independence was used to test the hypotheses. The findings of the study revealed that there was no significant relationship between techniques practised between the private and public junior secondary schools, however, there was a significant difference in the marks awarded to continuous assessment in both schools. Furthermore, the findings revealed that the method of implementation of continuous assessment is significantly different in both schools in the Benin metropolis. This study recommended that the state government through the Ministry of Education should put measures in place to ensure that continuous assessments carried out in schools by teachers are in line with recommended standards.